Photosynthetic rate and size structure of the phytoplankton community in transitional waters of the Northern Adriatic Sea - Mangoni, Olga; Bolinesi, Francesco; Saggiomo, Vincenzo; Saggiomo, Maria (Ecological Questions, 2020)
Transitional waters are among the most productive systems of the earth, supporting high rates of metabolism and primary production processes and providing important ecosystem services. In this study, we have investigated the effects of the freshwater input of the Po river on primary production processes in a coastal area influenced by the plume dispersion, using overall data derived from seven oceanographic cruises performed in seven different periods. In order to do this, PvsE (maximum rate of photosynthesis, P - vs light irradiance, E) curves with 14C were made for the determination of photosynthetic parameters, in association with the analyses of total phytoplankton biomass and size structure of the phytoplankton community, salinity and inorganic nutrient concentration. Stations were positioned according to salinity distribution from the coast to the off-shore waters. Data revealed that the water stratification mainly influenced the maximum Chl-a normalized photosynthetic rate (PBmax), total biomass and inorganic nutrients concentration. In the surface layer (0m), where the highest values of phytoplankton biomass were recorded, the micro- (>20µm) size class showed the highest photosynthetic rate and decreased toward off-shore waters. In the sub-surface layer, the nano- (>2 and <20µm) size class displayed the highest PBmax, probably linked to its capability to well photosynthesize under low light irradiance. The structure of the community in terms of size-classes was similar in both surface and deeper layer.